Peran public relation dalam membangun kepercayaan nasabah di lembaga keuangan syariah - Rosita, Halimatu (Maliki Interdisciplinary Journal, 2025)
In Indonesia, Islamic financial institutions are growing rapidly as the public becomes more aware of a financial system that adheres to Islamic principles. This study examines the role of Public Relations (PR) in building customer trust and the implementation of Sharia contracts such as Wakalah, Mudharabah, and Musyarakah, which serve as the basis for fair and transparent financing. Customer trust is a crucial element in maintaining interest in and loyalty to Islamic financial institutions. A sound PR strategy plays a crucial role in conveying Sharia values, strengthening the institution’s image, and increasing public understanding through ethical communication and the use of digital media. The study’s findings indicate that Sharia compliance, corporate social responsibility (CSR), and transparency are crucial components in building a positive image of Islamic financial institutions. However, challenges remain, such as low financial literacy, high perceived risk of profit-sharing investments, and reputational threats from ethical issues and cyberattacks. Therefore, collaboration between Islamic-based PR strategies, secure digital innovation, and the strict implementation of Sharia contracts is necessary to build sustainable customer trust and loyalty amidst the competition in the modern financial industry.